SE-590 Lab-Measured Reflectances (OTTER) - JOHNSON, L.F. (ORNL Distributed Active Archive Center, 1994)
Laboratory hemispherical reflectance spectra measurements taken to eliminate the effects of atmosphere, understory, exposed soils, mixed species and canopy architecture.